2024
DOI: 10.1016/j.jvoice.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Has the Prevalence of Creaky Voice Increased Among Finnish University Students From the 1990′S to the 2010′S?

Abstract: Everyday observations indicate that creaky voice has become common in Finland in recent years. Previous studies suggest that this trend is also occurring in other countries. This cross-sectional study investigates the use of creaky voice among Finnish university students from the 1990 0 s to the 2010 0 s. Material was obtained from a sound archive. It consisted of 200 samples from normophonic speakers (95 males, 105 females; mean age 23.7 years, SD 3.3 years, range 19−35 years). Normophonia was checked by two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, a large amount of vocal fry was detected in the recordings. It has been found that vocal fry has increased, especially among Finnish women [52]. Vocal fry and other non-modal voice qualities have been found to have an effect on learning outcomes, as it requires more cognitive capacity from the listener than listening to modal voice quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large amount of vocal fry was detected in the recordings. It has been found that vocal fry has increased, especially among Finnish women [52]. Vocal fry and other non-modal voice qualities have been found to have an effect on learning outcomes, as it requires more cognitive capacity from the listener than listening to modal voice quality.…”
Section: Discussionmentioning
confidence: 99%
“…Stimmgesunde erzeugen Vocal Fry, indem sie die wenig gespannt, verkürzt, dick und stark adduziert wirkenden Stimmlippen mit einem niedrigen subglottischen Anblasedruck in Schwingung versetzen. Die Stimmlippenschwingung ist hierbei verhältnismässig langsam und unregelmäßig, bei kleiner Schwingungsamplitude und verlängerter Schließphase 1 2 . Häufig sind die Taschenfalten sichtbar medialisiert.…”
Section: Wie Entsteht Vocal Fry?unclassified
“…B. Mandarin, betont werden. Somit kann Vocal Fry bei Stimmgesunden kurze oder lange sprachliche Abschnitte umfassen 2 3 . In Tonbeispielen 2 und 3 ist jeweils eine erwachsene Frau hörbar, bei der Vocal Fry je nach Sprache unterschiedlich stark auftritt ( Audio 2 , Audio 3 ).…”
Section: Wie Entsteht Vocal Fry?unclassified
See 1 more Smart Citation
“…62,63 On the other hand, an increase in f 0 after teachers' vocally loading working days has been reported. 44,64,65 It should also be noted that prevalence of creaky voice use (resulting in low f 0 ) has increased in young Finnish university students from the 1990's to the 2010's, particularly in females, 66 and has been reported to be up to 54% in some female teachers' speech. 44 However, in the present study we wanted to rule out creaky voice by setting the lower limit of fundamental frequency at 130 Hz in acoustic analysis.…”
Section: Acoustic Voice Parameters Within the Carryover And Trad Groupsmentioning
confidence: 99%